2022
DOI: 10.3390/ma15124072
|View full text |Cite
|
Sign up to set email alerts
|

LPBF Manufactured Functionally Graded Lattice Structures Obtained by Graded Density and Hybrid Poisson’s Ratio

Abstract: The additive manufacturing (AM) of innovative lattice structures with unique mechanical properties has received widespread attention due to the capability of AM processes to fabricate freeform and intricate structures. The most common way to characterize the additively manufactured lattice structures is via the uniaxial compression test. However, although there are many applications for which lattice structures are designed for bending (e.g., sandwich panels cores and some medical implants), limited attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The elasto-plastic response of material was defined with the isotropic hardening and linear hardening low. The erosion condition for the finite elements was defined according to the maximum tensile pressure criterion 35,57,58 . This criterion is recommended by the explicit materials library of ANSYS for different polymeric materials and in our previous work we found that this criterion provided good agreement with experimental data 33 .…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elasto-plastic response of material was defined with the isotropic hardening and linear hardening low. The erosion condition for the finite elements was defined according to the maximum tensile pressure criterion 35,57,58 . This criterion is recommended by the explicit materials library of ANSYS for different polymeric materials and in our previous work we found that this criterion provided good agreement with experimental data 33 .…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The considered design method has its origin in the so-called pantographic metamaterials 4,18,34,35 . These type of metamaterials consist of two families of the inclined beams placed with the offsets and interconnected at the intersections by the small pivots 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in additive manufacturing (AM) and selective laser melting (SLM) using biocompatible Ti-6Al-4V (Ti64) powder have expanded the applications of metal AM to medical implants. This advancement is primarily attributed to AM's capability to produce complex geometries that were not possible using conventional subtractive manufacturing [1][2][3][4]. Additively manufactured patient-specific medical devices have the benefit of matching individual patient's bone anatomy due to the high customizability of AM process [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in ensuring the designed structure meets the strength requirements while saving as much materials as possible, the relative density is designed differently in various regions. To date, most research interests involving this FGLSs using SLM fabrication have been concentrated on the effects of cellular structural types and metallic types on mechanical properties [ 13 , 14 , 15 , 16 , 17 ]. Mingkang Zhang et al [ 18 ] designed and fabricated body-center-cubic (BCC) FGLSs based on Ti6Al4V alloy.…”
Section: Introductionmentioning
confidence: 99%